Evaluation of Quality of Life at Progression in Patients with Soft Tissue Sarcoma. (23rd April 2017) - Hudgens, Stacie; Forsythe, Anna; Kontoudis, Ilias; D'Adamo, David; Bird, Ashley; Gelderblom, Hans
Abstract : Introduction . Soft Tissue Sarcoma (STS) is a rare malignancy of mesodermal tissue, with international incidence estimates between 1.8 and 5 per 100, 000 per year. Understanding quality of life (QoL) and the detrimental impact of disease progression is critical for long-term care and survival. Objectives . The primary objective was to explore the relationship between disease progression and health-related quality of life (HRQoL) using data from Eisai's study (E7389-G000-309). Methods . This was a 1 : 1 randomized, open-label, multicenter, Phase 3 study comparing the efficacy and safety of eribulin versus dacarbazine in patients with advanced STS. The QoL analysis was conducted for the baseline and progression populations using the European Organization for Research and Treatment of Cancer 30-item core QoL questionnaire (EORTC QLQ-C30). Results . There were no statistical differences between the two treatment arms at baseline for any domain (p > 0.05 ;n = 452 ). Of the 399 patients who experienced disease progression (unadjusted and adjusting for histology), dacarbazine patients had significantly lower Global Health Status, Physical Functioning scores, and significantly worse Nausea and Vomiting, Insomnia, and Appetite Loss (p < 0.05 ). Conclusions . These results indicate differences in HRQoL overall and at progression between dacarbazine and eribulin patients, with increases in symptom severity observed among dacarbazine patients.